The ECtHR and Mental Health Jurisprudence: Progressive Interpretation or Doctrinal Stagnation? - Widlas-Klimsiak, Katarzyna (PRAWO i WIĘŹ, 2025)
This paper asks whether the European Court of Human Rights (ECtHR) has driven a rights-based transformation of mental-health law, or merely refined a paternalistic status quo. Using doctrinal analysis of the ECHR and close reading of leading judgments, it situates Strasbourg case law within the Council of Europe’s normative framework (European Social Charter, Oviedo Convention) and soft-law developments, read against the CRPD. Three core findings emerge. First, the Court has thickened procedural protections under Articles 5 and 3, tightening admission standards, extending review to informal and social-care placements, and recognising therapeutic neglect as ill-treatment, while Article 8 jurisprudence increasingly foregrounds bodily integrity and participation. Second, non-consensual treatment is still treated largely as an incident of lawful detention, with deference to clinical expertise and risk-based reasoning; autonomy and equal legal capacity remain weak constraints. Third, Council of Europe soft law and equality norms outpace binding doctrine, endorsing deinstitutionalisation, informed consent, and supported decision-making. The paper prescribes recalibration: analytically decoupling detention from treatment, with capacity-sensitive review under Articles 3 and 8; enforcing rigorous least-restrictive-alternative tests, and integrating Article 14 scrutiny to expose structural discrimination.